2017
DOI: 10.1007/s10551-017-3616-1
|View full text |Cite
|
Sign up to set email alerts
|

How and When Retailers’ Sustainability Efforts Translate into Positive Consumer Responses: The Interplay Between Personal and Social Factors

Abstract: This study aims to address how (through which mechanisms) and when (under which conditions) retailers' sustainability efforts translate into positive consumer responses. Hypotheses are developed and tested through a scenario-based experiment among 672 consumers. Retailers' assortment sustainability and distribution sustainability are manipulated. Retailers' sustainability efforts lead to positive consumer responses (e.g., improved store evaluations) via two underlying mechanisms: consumers' identification with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 91 publications
0
33
0
4
Order By: Relevance
“…Research has demonstrated that firms' sustainable efforts have a decisive effect on consumers' responses [53,54]. Moreover, moral emotion attributions are an important impetus for people's actions [47].…”
Section: Moderation Of Destination Social Responsibility (Dsr)mentioning
confidence: 99%
“…Research has demonstrated that firms' sustainable efforts have a decisive effect on consumers' responses [53,54]. Moreover, moral emotion attributions are an important impetus for people's actions [47].…”
Section: Moderation Of Destination Social Responsibility (Dsr)mentioning
confidence: 99%
“…Research based on TPB suggested the correlation between consumer purchase intention and purchase behavior is strong (Ajzen, 2011). Though some research has confirmed that the behavioral intention is a prominent factor for actual behavior, the actual behavior often differs because the consumer does not always follow through on the intention, especially in unique settings when presented with options or given restrictions (Hofenk, van Birgelen, Bloemer, & Semeijn, 2017;Wang, Lin, & Li, 2018). Based on the previous literature, remanufactured products may provide one of these settings in that intention is inconsistent with actual behavior (Khor & Hazen, 2017).…”
mentioning
confidence: 99%
“…There is an increased need for reduction in food waste and achieving total utilization of all biomasses, and for this purpose, new and more circular value chains will have to be created [50,51]. In addition, an increasing focus on sustainability is observed in the society, in general [52]. The emphasis is shifting towards maximizing value creation in all parts of the food supply chain to ensure a sustainable and profitable industry, with a focus on keeping components at their highest value at all times, while reducing waste to a minimum [51].…”
Section: Market-driven Innovation In Functional Foodmentioning
confidence: 99%